Analisis Pengaruh Jam Kerja dan Pendapatan Rumah Tangga terhadap Kemampuan Pemulung dalam Memenuhi Kebutuhan Hidup di TPA Gunung Tugel - Laksita, Anindya; Sugito, Sugito; Sudjarwanto, Sudjarwanto (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The purpose of this research to recognize the work time influence for the income, how the influence of their household income and the insurance number of the consumption expense. We can see that the household revenue can complete their necessary life and can see the household status based on the poor household criteria according to BPS. The population in this research is the recycler in TPA(Tempat Pembuangan Akhir) Gunung Tugel. The respondent number of this research is 72 respondents. The respondent number determination done by sensus method. It used descriptive analysis method with intersecting tabulation and frequency distribution list. From the result of it, the data analysis shows that: (1) The work time has positive effect to their income, (2) The household income and the insurance amount of recycler’s family has positive influence to household consumption expenditure, (3) There are 22 (30,56%) from 72 respondent who can’t suffice necessary.